Experiment Of Speed Control For An Electric Trishaw Based On Pid Control Algorithm - Saat, Shahrizal; Fikri, Mohd Nabil; Mohd Tumari, Mohd Zaidi; Abdul Kadir, Ahmad Muzaffar; Abd Rashid, Wan Norhisyam; Wan Hamat, Wan Hassan (IJENS Publisher, 2017)
-